2012
DOI: 10.1146/annurev-publhealth-031811-124624
|View full text |Cite
|
Sign up to set email alerts
|

Quitlines and Nicotine Replacement for Smoking Cessation: Do We Need to Change Policy?

Abstract: In the past 20 years, public health initiatives on smoking cessation have increased substantially. Randomized trials indicate that pharmaceutical cessation aids can increase success by 50% among heavier smokers who seek help, and use of these aids has increased markedly. Quitlines provide a portal through which smokers can seek assistance to quit and are promoted by tobacco control programs. Randomized trials have demonstrated that telephone coaching following a quitline call can also increase quitting, and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 69 publications
0
42
0
Order By: Relevance
“…Because there may be some small continuing decline in quit rates beyond 4 years, 6% probably reflects the upper limit of long‐term medication benefit to smokers under ideal RCT conditions. Under real‐world conditions, the benefit of these medications is likely to be lower than in the context of trials, due to poorer adherence to treatment protocol and fewer patient/provider interactions in real‐world settings than in RCTs 36, 37, 38.…”
Section: Discussionmentioning
confidence: 99%
“…Because there may be some small continuing decline in quit rates beyond 4 years, 6% probably reflects the upper limit of long‐term medication benefit to smokers under ideal RCT conditions. Under real‐world conditions, the benefit of these medications is likely to be lower than in the context of trials, due to poorer adherence to treatment protocol and fewer patient/provider interactions in real‐world settings than in RCTs 36, 37, 38.…”
Section: Discussionmentioning
confidence: 99%
“…This exploratory analysis was motivated, in part, by conflicting findings about the effects of cessation medication in real-world contexts. While such medications have produced evidence of benefit in some studies, such as those examining medication effects in over-the-counter contexts (Fiore et al, 2008;Shiffman and Sweeney, 2008), some survey and longitudinal studies have found little evidence that medication use is associated with greater likelihood of successful cessation (e.g., Messer et al, 2008;Pierce, Cummins, White, Humphrey, & Messer, 2012). Among 278 participants who completed the 1-month follow-up, 72 reported using a cessation medication.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…It has also been suggested that the promotion of cessation aids by pharmaceutical companies may imply that quitting without formal assistance is more difficult than it is, thereby undermining smokers' willingness to try to quit and their belief in their ability to stop (Chapman & MacKenzie, 2010;Pierce et al, 2012;Zhu et al, 2012) Chapman and McKenzie argue that unassisted quitting, or "cold turkey", has the greatest impact on reducing smoking prevalence and accordingly should receive greater clinical and research attention (Chapman & MacKenzie, 2010).…”
Section: Chapter 6 Why Don't Smokers Want Help To Quit? a Qualitativmentioning
confidence: 99%
“…They argue that the pharmaceutical industry has a vested interest in promoting the view that quitting is difficult without medical help, thereby making smokers think that quitting is harder than it is. These concerns are shared by researchers in the USA (Pierce, Cummins, White, Humphrey, & Messer, 2012). An opposite concern has been expressed about the unintended consequences of increased availability and promotion of medicines for smoking cessation, namely that it may lead smokers to believe that there are 'magic bullets' for nicotine addiction that will enable them to quit easily should they choose to do so (Dingel et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation